Methodology for sampling and detection of airborne coronavirus including SARS-CoV-2. Issue 5 (June 2022) - Yun, Hyunjun; Yang, Jinho; Seo, Ji-Hoon; Sohn, Jong-Ryeul
In recent years, several epidemics by transmissible respiratory viruses have emerged, especially pandemics caused by coronaviruses. The most significant public health emergency may be the COVID-19 pandemic. Identifying the transmission of infectious disease plays an important role in healthcare for protecting and implementing effective measures for public health. However, studies on SARS-CoV-2 transmission dynamics are lacking. Infection with the airborne virus is very important and airborne transmission is likely to cause major problems. However, research on the aerosol route of the virus is very limited. Here, we aimed to present airborne coronavirus detection methods in previous studies and address the importance of methodology for the future. In previous studies on airborne coronavirus, detection methods were different in each study. Therefore, comparison between the airborne virus detected in each study is impossible, and the risk assessment could not be properly analysed due to limitations in applying it as basic data. There is currently a risk assessment for coronavirus, but the risk assessment due to airborne transmission is insufficient. Therefore, recommending accurate guidelines for airborne transmission is difficult. Future research should be conducted to standardize airborne virus detection methods to prevent transmission through rapid risk assessment and monitoring.